2012
DOI: 10.1007/s00784-012-0847-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of artificial demineralization bordering different types of laminate veneers using visual inspection and storage phosphor radiography

Abstract: Early detection of enamel demineralizations bordering laminate veneers would result in time-saving and less-invasive treatment methods; therefore, SPP radiography may be recommended in clinically suspicious cases since it provides better diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Marginal staining was assessed by observing digital images, similar to other studies reported in the literature 5,14 . Standardized images of the mesial, distal, incisal and cervical margins of each restoration were used for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Marginal staining was assessed by observing digital images, similar to other studies reported in the literature 5,14 . Standardized images of the mesial, distal, incisal and cervical margins of each restoration were used for evaluation.…”
Section: Discussionmentioning
confidence: 99%